Integrated analysis of costs and amount of greenhouse gases emissions during the building lifecycle - Krzysztof Zima (Archives of Civil Engineering, 2021)
More than 6 billion square metres of new buildings are built each year. This is about 1.2 million buildings. If we translate these figures into carbon footprint (CF) generated during the construction, it will be approximately 3.7 billion tons of carbon dioxide. The contractors all over the world – also in Poland – decide to calculate the carbon footprint for various reasons, but mostly they are compelled to do so by the market. The analysis of costs and emissions of greenhouse gases for individual phases of the construction system allows implementing solutions and preventing a negative impact on the environment without increasing the construction costs. The share of each phase in the amount of produced carbon for construction and use of the building depends mainly on the used materials and applied design solutions. Hence, the materials and solutions with lesser carbon footprint should be used. It can be achieved by using natural materials or materials which do not need much energy to be produced. The author will attempt to outline this idea and present examples of integrated analysis of costs and amount of carbon footprint during the building lifecycle.